Proton pencil beam scanning for mediastinal lymphoma: the impact of interplay between target motion and beam scanning. (19th March 2015) - Zeng, C; Plastaras, J P; Tochner, Z A; White, B M; Hill-Kayser, C E; Hahn, S M; Both, S
Abstract: The purpose of this study was to assess the feasibility of proton pencil beam scanning (PBS) for the treatment of mediastinal lymphoma. A group of 7 patients of varying tumor size (100–800 cc) were planned using a PBS anterior field. We investigated 17 fractions of 1.8 Gy(RBE) to deliver 30.6 Gy(RBE) to the internal target volume (ITV). Spots with σ ranging from 4 mm to 8 mm were used for all patients, while larger spots ( σ  = 6–16 mm) were employed for patients with motion perpendicular to the beam (⩾5 mm), based on initial 4-dimensional computed tomography (4D CT) motion evaluation. We considered volumetric repainting such that the same field would be delivered twice in each fraction. The ratio of extreme inhalation amplitude and regular tidal inhalation amplitude (free-breathing variability) was quantified as an indicator of potential irregular breathing during the scanning. Four-dimensional dose was calculated on the 4D CT scans based on the respiratory trace and beam delivery sequence, implemented by partitioning the spots into separate plans on each 4D CT phase. Four starting phases (end of inhalation, end of exhalation, middle of inhalation and middle of exhalation) were sampled for each painting and 4 energy switching times (0.5 s, 1 s, 3 s and 5 s) were tested, which resulted in 896 dose distributions for the analyzed cohort. Plan robustness was measured for the target and critical structures in terms of the percent difference between 'delivered' dose (4D-evaluated) and planned dose (calculated on average CT). It was found that none of the patients exhibited highly variable or chaotic breathing patterns. For all patients, the ITV D 98 % was degraded by <2% (standard deviations ∼ 0.1%) when averaged over the whole treatment course. For six out of seven patients, the average degradation of ITV D 98 % per fraction was within 5% . For one patient with motion perpendicular to the beam (⩾5 mm), the degradation of ITV D 98 % per fraction was up to 15%, which was mitigated to 2% by employing larger spots and repainting. Deviation of mean lung dose was at most 0.2 Gy(RBE) (less than 1% of prescribed dose, 30.6 Gy(RBE)), while the deviation of heart maximum dose and cord maximum dose could exceed 5% of the prescribed dose. No significant difference in either target coverage or normal tissue dose was observed for different energy switching times compared via two-sided Wilcoxon signed-rank tests ( p  < 0.05). This feasibility study demonstrates that, for mediastinal lymphoma, the impact of the interplay effect on the PBS plan robustness is minimal when volumetric repainting and/or larger spots are employed.